The innovation of government bonds in the growth of an emergent capital market - Cordelia Onyinyechi Omodero; Philip Alege (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The growth of an emerging capital market is necessary and requires all available resources and inputs from various sources to realize this objective. Several debates on government bonds' contribution to Nigeria's capital market developmental growth have ensued but have not triggered comprehensive studies in this area. The present research work seeks to close the breach by probing the impact of government bonds on developing the capital market in Nigeria from 2003-2019. We employ total market capitalization as the response variable to proxy the capital market, while various government bonds serve as the independent variables. The inflation rate moderates the predictor components. The research uses multiple regression technique to assess the explanatory variables' impact on the total market capitalization. At the same time, diagnostic tests help guarantee the normality of the regression model's data distribution and appropriateness. The findings reveal that the Federal Government of Nigeria's (FGN) bond is statistically significant and positive in influencing Nigeria's capital market growth. The other predictor variables are not found significant in this study. The study suggests that the Government should improve on the government bonds' coupon, while still upholding the none default norm in paying interest and refunding principal to investors when due.
Keywords: 650; capital market; FGN bonds; government bonds; total market capitalization